Digitalization and Religious Moderation: A New Direction for Islamic Religious Education Policy in the Era of Disruption - Masniatul Ilmiah; Khoirul Anwar; Umi Farihah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The era of digital disruption demands a reformulation of Islamic Religious Education (IRE) policy in order to respond to the challenges of globalization of values and technological developments. This article aims to analyze the new direction of PAI policy through the integration of digitalization and religious moderation. The method used is a literature review (LR) with a qualitative approach. Data were obtained from 30 scientific articles published between 2021 and 2025 through Google Scholar and Publish or Perish (PoP), which were selected into 5 relevant main articles. The results of the study show that digitalization plays a strategic role in expanding access to inclusive and interactive religious learning, while religious moderation acts as a filter of values to maintain spiritual and moral balance amid the rapid flow of information. The integration of the two gives rise to a new paradigm of PAI policy that is oriented towards values, technology, and humanism. This policy requires the strengthening of a moderate digital-based curriculum, the improvement of religious digital literacy competencies for teachers, and educational governance that is responsive to the challenges of cyber radicalism. Thus, the new direction of PAI policy needs to be directed towards the synergy between digital transformation and the internalization of Islamic wasathiyah values in order to shape a generation of Muslims who are digitally literate, moderate in character, and globally competitiv.